Occupational hazard self-evaluation module intervention for safety leadership and safety knowledge-attitude-behaviour among small and medium manufacturing workers - Zulkifly, Syazwan Syah (2022)
Small and Medium Enterprises (SMEs) contribute to at least 70% of workplace accidents in Malaysia. Financial and human resource limitations have been found to be the main causes and a tailored approach is needed to overcome the problem. Previous literature has revealed that unsatisfactory safety behaviour is the leading cause of workplace accidents and safety leadership has been identified as the most effective solution. Besides, safety knowledge and safety attitude have been found to have substantial influence on workers’ safety behaviour. This research aims to develop an intervention module, known as the Occupational Hazard Self-Evaluation Module (OHSEM), focusing on the supervisor’s safety leadership roles, namely safety coaching, safety concern, and safety monitoring, in nurturing safety KAB. The contents particularly focus on improving the ability of self-evaluating occupational hazards by workers. Subsequently, the intervention module was tested on the small manufacturing firms to evaluate its effectiveness in improving safety knowledge-attitude-behaviour (KAB) among manufacturing workers of SME. The phase one of the research applied a cross- sectional design involving 300 SME manufacturing workers in the Northern Corridor Economic Region (NCER) of Malaysia. The level of safety KAB was determined according to the mean values. Moreover, the nature of relationship between safety leadership variables and safety KAB was explored by using Partial Least Squares- Structural Equation Modelling (PLS-SEM) - Higher-Order Construct Analysis. In the second phase, the design and development of OHSEM was carried out and its usability and validity evaluation were performed via Modified Fuzzy Delphi (FDM) method, involving 15 experts. For the third phase, a quasi-experimental study with a control group was conducted involving a total of 200 workers. A pre- and post-test was undertaken and descriptive and inferential analyses (t-test, ANCOVA, and regression) were applied for this phase to evaluate the module’s effectiveness.The results of Phase 1 show a moderate level of safety KAB, confirming the necessity of developing the intervention module. Moreover, safety leadership directly influences safety behaviour, with safety knowledge and safety attitude mediating the relationship. In Phase 2, the FDM results show the average threshold values for the importance and appropriateness of OHSEM contents are below 0.2 and the overall percentages of each item evaluated by the panellists is greater than 75%, indicating a fair degree of OHSEM’s usability and validity. Lastly, in Phase 3, a significant difference in terms of safety KAB between the intervention group and the control group (p<0.05) is revealed. Furthermore, the regression results indicate the R2 value of 0.721 for post-test compared to 0.149 for pre- test in terms of the relationship between safety leadership and safety KAB. Moreover, the effect size of the intervention group for safety KAB is vast (d> 1.4), compared to the control group, which is small (d<0.2). This research proves the effectiveness of OHSEM when the level of safety KAB significantly increases with the effect size of d=3.54 for post-intervention compared to d=0.18 for pre-intervention. Moreover, the significant difference of mean values between the intervention and control group for safety KAB (p<0.05) affirm the effectiveness of OHSEM.